MERAIH SUKSES PARENTING DI ERA GEN – Z MELALUI PERNIKAHAN BERKUALITAS : MEMBANGUN FONDASI KELUARGA YANG KOKOH : Pernikahan berkualitas untuk meraih parenting yang sukses - Carmelia Puteri Hendarsyah; Mirna Nur Alia Abdullah (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2024)
The importance of building a solid family foundation is one of the keys to achieving success in marriage and parenting in the Gen - Z era. One way to achieve this is through a quality marriage. The aim is to provide insight and knowledge for prospective parents in strengthening their future marriage relationships which will create a healthy family environment and support parenting thinking from the perspective of the growth of Gen - Z children. Using literature study and observation methods. Researchers looked for various sources in the form of journals, articles, books and interviews with several parties concerned in discussing the article entitled ACHIEVE PARENTING SUCCESS IN GEN - Z THROUGH QUALITY MARRIAGE: BUILDING A SOLID FAMILY FOUNDATION. The results of the research explain that a marriage can be said to be successful because each bride and groom are ready and then approved by both parties, marry well, in accordance with existing procedures and live a good life as husband and wife, able to carry out their respective functions and roles each one well.